2013 Ieee Ro-Man 2013
DOI: 10.1109/roman.2013.6628517
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the influence of culture on proxemic behaviors for humanoid robots

Abstract: In social robotics, the behavior of humanoid robots is intended to be designed in a way that they behave in a human-like manner and serve as natural interaction partners for human users. Several aspects of human behavior such as speech, gestures, eye-gaze as well as the personal and social background of the user need therefore to be considered. In this paper, we investigate interpersonal distance as a behavioral aspect that varies with the cultural background of the user. We present two studies that explore wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 9 publications
2
29
0
Order By: Relevance
“…This draws on the notion of proxemics, the interpersonal distance between people [15], but has also been shown to apply between people and robots [11]. Our study demonstrated that if the quadcopter gets too close to the jogger, it immediately shifts any focus, even if it is just from a safety perspective.…”
Section: Dimension 2: Focusmentioning
confidence: 69%
“…This draws on the notion of proxemics, the interpersonal distance between people [15], but has also been shown to apply between people and robots [11]. Our study demonstrated that if the quadcopter gets too close to the jogger, it immediately shifts any focus, even if it is just from a safety perspective.…”
Section: Dimension 2: Focusmentioning
confidence: 69%
“…A number of studies support the hypothesis that people from different cultures not only (i) have different preferences concerning how the robot should be and behave [6], but also (ii) tend to prefer robots better complying with the social norms of their own culture, both in the verbal [10], [11] and non-verbal behaviour [12], [8]. This preference does not merely affect the robot's likeability.…”
Section: B Cultural Competence In Robotics Until Todaymentioning
confidence: 98%
“…In 2013, in a series of experiments involving Arab and German participants, people were asked to place a Nao robot at a suitable distance to hold a conversation with them [1]. None of the participants was used to interact with a robot on a daily basis, but they all had plenty of experience in talking with other people.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of a person's culture on his attitude towards, and preferences in the interaction with, a robot is the subject of relevant and ongoing research [2]. So far, literature findings suggest that people from different cultures not only have different preferences concerning how the robot should be and behave [3], but also tend to prefer a robot that better complies with the social norms of their own culture, in aspects such as the verbal [4], [5], [6] and non-verbal behaviour [7] and the interpersonal distance [1], [8].…”
Section: Introductionmentioning
confidence: 99%